Laminar fluid ejection device enables high yield and preservation of mRNA and SaRNA LNP formulations - Chia Hao Ho; Irafasha C. Casmil; Manu Sharma; Tim Rees; Kenza Enright; Nick Allan; Anna K. Blakney (Scientific Reports)
Abstract The development of messenger RNA (mRNA) and self-amplifying RNA (saRNA) vaccines has revolutionized modern vaccinology, particularly with the success of lipid nanoparticle (LNP)-based SARS-CoV-2 vaccines. Intranasal administration offers a promising approach for respiratory vaccines, providing mucosal immunity at the primary entry site of pathogens. However, the impact of different aerosolization delivery systems on RNA-LNP stability, recovery volume and functionality is not well understood. In this study, we compare the effects of three intranasal administration devices- a commercial Nebulizer, a commercial Spray, and a Laminar Fluid Ejection (LFE) Device developed by Rocket Science Health- on LNP physicochemical properties, RNA encapsulation efficiency, and functional protein expression level. Our findings demonstrate that high shear forces in the commercial nebulizer delivery system significantly increase LNP particle size (85 nm to 300 nm) and polydispersity index (PDI), leading to RNA degradation and reduced encapsulation efficiency (100–39%). Conversely, the LFE Device preserved LNP structural integrity, achieving the highest RNA encapsulation efficiency (94% for mRNA, 102% for saRNA) and superior functional protein expression (3-fold higher luciferase activity compared to the CM Nebulizer). These results highlight the importance of selecting an appropriate delivery system to optimize RNA-LNP delivery and retention in intranasal applications. Our study supports the LFE Device as a viable candidate for effective RNA-LNP-based mucosal vaccine administration, with potential applications in next-generation RNA therapeutics.